2022
DOI: 10.3847/1538-4357/aca085
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Radio-loud Narrow-line Seyfert 1 Galaxy at z = 0.9 Reddened with a Strong 2175 Å Bump

Abstract: We present a broadband spectrophotometric analysis of an unusual quasar, SDSS J160558.86+474300.1, at z = 0.9, found in a systematic search for reddened radio-loud narrow-line Seyfert 1 galaxies (NLS1s). J1605+4743 qualifies for the conventional definition of an NLS1 in its permitted emission line widths and Hβ/[O iii] flux ratio. It also shows strong Fe ii emissions. J1605+4743 has a steep radio spectrum. With a radio loudness of ∼150 (70) before (after) reddening correction, it is among the most radio-loud N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 101 publications
1
0
0
Order By: Relevance
“…By carefully decomposing the BELs of a LoBAL quasar (SDSS J163345.22+512748.4), Liu et al (2019) tentatively identified a blueshifted component in both Hα and Hβ BELs, with their velocities possibly consistent with that of Mg II. A similar Hα profile was also identified in a reddened quasar (SDSS J160558.86 +474300.1; Zhou et al 2022). J1540+4923 might be an extreme case of these rarities and deserve further studies.…”
Section: Implication and Future Worksupporting
confidence: 67%
“…By carefully decomposing the BELs of a LoBAL quasar (SDSS J163345.22+512748.4), Liu et al (2019) tentatively identified a blueshifted component in both Hα and Hβ BELs, with their velocities possibly consistent with that of Mg II. A similar Hα profile was also identified in a reddened quasar (SDSS J160558.86 +474300.1; Zhou et al 2022). J1540+4923 might be an extreme case of these rarities and deserve further studies.…”
Section: Implication and Future Worksupporting
confidence: 67%